Endosialin defines human stem Leydig cells with regenerative potential. Issue 10 (20th September 2020) - Xia, Kai; Ma, Yuanchen; Feng, Xin; Deng, Rongda; Ke, Qiong; Xiang, Andy Peng; Deng, Chunhua
Abstract: STUDY QUESTION: Is endosialin a specific marker of human stem Leydig cells (SLCs) with the ability to differentiate into testosterone-producing Leydig cells (LCs) in vitro and in vivo ? SUMMARY ANSWER: Endosialin is a specific marker of human SLCs which differentiate into testosterone-producing LCs in vitro and in vivo . WHAT IS KNOWN ALREADY: Human SLCs have been identified and isolated using the marker platelet-derived growth factor receptor α (PDGFRα) or nerve growth factor receptor (NGFR). However, the specificity was not high; thus, LCs and germ cells could be mistakenly sorted as SLCs if PDGFRα or NGFR was used as a marker for human SLCs isolation. STUDY DESIGN, SIZE, DURATION: Firstly, we re-evaluated the specificity of PDGFRα and NGFR for SLCs in adult human testes. Then we analysed the previously published single-cell sequencing data and found that endosialin may identify human SLCs. Subsequently, we sorted endosialin + cells from four human donors and characterized their self-renewal and multipotent properties. To assess whether endosialin + cells have the potential to differentiate into functional LCs in vitro, these cells were stimulated by differentiation-inducing medium. We next assessed the in vivo regenerative potential of human endosialin + cells after xenotransplantation into the testes of immunodeficient mice. PARTICIPANTS/MATERIALS, SETTING, METHODS: Single-cell sequencing analysis, immunofluorescence and flow cytometry were used to characterize human testis tissues. In vitro colony formation, multipotent differentiation (adipogenic, osteogenic and chondrogenic) and Leydig cell-lineage induction were used to assess stem cell activity. Xenotransplantation into 3-week-old immunodeficient mice was used to determine in vivo regenerative potential. Endpoint measures included testosterone measurements, cell proliferation, immunofluorescence, flow cytometry and quantitative RT–PCR. MAIN RESULTS AND THE ROLE OF CHANCE: The results indicate that endosialin is a specific marker of SLCs compared with PDGFRα and NGFR. Additionally, endosialin + cells isolated from human testes show extensive proliferation and differentiation potential in vitro : their self-renewal ability was inferred by the formation of spherical clones derived from a single cell. Moreover, these cells could differentiate into functional LCs that secreted testosterone in response to LH in a concentration-dependent manner in vitro . These self-renewal and differentiation properties reinforce the proposal that human testicular endosialin + cells are SLCs. Furthermore, transplanted human endosialin + cells appear to colonize the murine host testes, localize to peritubular and perivascular regions, proliferate measurably and differentiate partially into testosterone-producing LCs in vivo . LARGE SCALE DATA: NA. LIMITATIONS, REASONS FOR CAUTION: Owing to the difficulty in collecting human testis tissue, the sample size was limited. The functions of endosialin on SLCs need to be elucidated in future studies. WIDER IMPLICATIONS OF THE FINDINGS: A discriminatory marker, endosialin, for human SLCs purification is a prerequisite to advance research in SLCs and logically promote further clinical translation of SLCs-based therapies for male hypogonadism. STUDY FUNDING/COMPETING INTEREST(S): A.P.X. was supported by the National Key Research and Development Program of China (2017YFA0103802 and 2018YFA0107200). C.D. was supported by the National Natural Science Foundation of China (81971314) and the Natural Science Foundation of Guangdong Province, China (2018B030311039). The authors declare no conflict of interest.